Variability in micronekton active carbon transport estimates on the Southwest Coast of Oahu using three different sampling gears - Kwong, Lian E.; Bahl, Alexis A.; Pakhomov, Evgeny A. (Frontiers in Marine Science, 2022)
Micronekton were sampled off the southwest coast of Oahu in October of 2004 as part of the North Pacific Marine Sciences Organization (PICES) Micronekton Sampling Gear Intercalibration experiment (MIE-1). The initiative employed three different micronekton sampling gears: the Cobb Trawl, Isaacs–Kidd midwater trawl (IKMT), and Hokkaido University frame trawl (HUFT). Micronekton catches from the three sampling gears were used to quantify the rates of active carbon transport. We evaluate the differences in total active carbon transport assessed using the data collected by the three gears, with a particular emphasis on taxa- and length-specific differences across gears. The estimates of total active carbon transport derived from the HUFT were significantly lower than those derived from the IKMT. We detected no significant difference between estimates derived using the IKMT and Cobb and the Cobb and HUFT. Dominant groups contributing to active carbon transport varied across sampling gears (Cobb: myctophids and cephalopods; HUFT: decapods and stomatopods; IKMT: cephalopods, myctophids, and decapods); however, no significant differences in the contribution of individual taxa to active carbon transport across sampling gears were detected (e.g., the myctophid active carbon transport contribution for the Cobb was not significantly different from that of the IKMT). Pairwise ratios revealed size-specific differences in the contribution to total flux across gears. As expected, the HUFT and IKMT estimates of active carbon transport were higher for smaller size classes, while estimates from the Cobb were more evenly distributed across size classes. These findings suggest that the differences in total active carbon transport from the three sampling gears are driven primarily by size-based sampling biases, which produce significant differences in biomass estimates. This study provides a foundation upon which future active carbon transport studies may be adjusted to address sampling gear biases.